School Counselors' Persuasive Communication in Shaping Students' Character at SMAN 38 Jakarta - Selamat Ginting; Nuriyati Samatan; Daryani Daryani; Agus Salim (Greenation Education and Culture Review, 2026)
Guidance and Counseling (BK) teachers are one of the essential elements in student development across almost all school levels in Indonesia. BK teachers serve as "confidants" at school and act as second parents. This study aims to determine the forms of persuasive communication used by BK teachers in shaping positive student character at SMAN 38 Jakarta. The research utilizes Ivan Petrovich Pavlov's Behaviorism Theory. The results show a shift in the paradigm and role of BK teachers today compared to the past. While BK teachers were previously viewed as "School Police," they now serve as friends to students on one hand and as enforcers of discipline on the other. Consistency in rules and policies, along with their implementation, makes the task of BK teachers easier in shaping positive student character. Out of the four analyzed assumptions of Pavlov, this study finds that three assumptions can be implemented, while one assumption regarding internal thoughts can be disregarded; however, in this study, the students' internal thoughts are not ignored. BK teachers provide space and time for students to express their problems, act as good listeners, and offer solutions when needed. This approach has strengthened relationships and built positive student character, as students feel valued and heard.